Efficacy of local anaesthetic cocktail infiltration in a total knee replacement: a prospective, randomized study - Kulkarni, Ameya U.; Kulkarni, Umesh M. (International Journal of Research in Orthopaedics, 2020)
Background: The aim of this study is to assess the efficacy of local anaesthetic cocktail infiltration in pain management during a total knee arthroplasty. Methods: In this study we had 25 patients each in study and control group. The study group was infiltrated with the local anesthetic cocktail just before final implantation. Pain was documented by a visual analogue scale in a double blinded manner. Statistical significance was calculated using an unpaired “t” test. Results: In study group, pain levels were significantly lower as compared to control group for the first 48 hours after surgery with a ‘p’ value of 0.0224 (<0.05). The need of intravenous tramadol for breakthrough pain on the second day was significantly lower in study group as compared to control group with a ‘p’ value of 0.033(<0.05). Conclusions: This study shows that the local high volume anaesthetic infiltration is effective in reducing immediate postoperative pain and the need of IV opioids for the first 48 hours after surgery.